2010
DOI: 10.1002/ejlt.201000122
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐oxazoline)s based on fatty acids

Abstract: Poly(2-oxazoline)s are an interesting class of synthetic poly(amide) s that can be prepared by living cationic ring-opening polymerization. The properties of poly(2-oxazoline) s can be tuned by variation of the 2-substituent of the 2-oxazoline monomer. In this contribution the utilization of fatty acids as side chains for poly(2-oxazoline) s is highlighted. The incorporation of such long aliphatic side-chains results in hydrophobic crystalline poly(2-oxazoline) s that are often applied for the preparation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 86 publications
(110 reference statements)
1
28
0
2
Order By: Relevance
“…2‐(9‐Decenyl)‐2‐oxazoline was modified by thiol‐ene coupling in the presence of 2‐mercaptoethanol giving polyols for polyurethane formulations 110. The unsaturated parts of the soy‐based 2‐oxazoline monomer have been employed to crosslink the cores of micelles under UV‐irradiation 114, 115. The same strategy has been used with tetrathiol in order to elaborate novel photoresists 116.…”
Section: Functionalized Monomersmentioning
confidence: 99%
“…2‐(9‐Decenyl)‐2‐oxazoline was modified by thiol‐ene coupling in the presence of 2‐mercaptoethanol giving polyols for polyurethane formulations 110. The unsaturated parts of the soy‐based 2‐oxazoline monomer have been employed to crosslink the cores of micelles under UV‐irradiation 114, 115. The same strategy has been used with tetrathiol in order to elaborate novel photoresists 116.…”
Section: Functionalized Monomersmentioning
confidence: 99%
“…Aspects of advanced macromolecular engineering of polyoxazolines, including side-and end-chain functionalization, synthesis and properties of block and random copolymers, etc., have very recently been assorted by Hoogenboom [9,10], Schlaad et al [11], and Makino and Kobayashi [12]. The use of fatty acid based monomers for the preparation of sustainable poly(2-oxazoline)s was also recently highlighted by Hoogenboom [13].…”
Section: Introductionmentioning
confidence: 98%
“…Not considered are other emerging applications of poly(2-oxazoline)s, for instance in the fields of biomedicine and life sciences, where POXylation is being successfully introduced as an alternative to PEGylation [14], which has very recently been reviewed elsewhere [15]. Rather than trying to present a comprehensive overview of the literature as was done in other recent articles [9][10][11][12][13], it is aimed to introduce the importance and potential of bioinspired poly(2-oxazoline)s based on selected key references from the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] The chemical versatility of fatty acids, i.e., different chain length and amount of double bonds, has been exploited for the fabrication of various monomers as basis for the synthesis of well-defined polymers. [4,5] In addition, the double bond functionalities have been utilized for post-modification reactions of the resulting materials, such as cross-linking and thiolene reactions. [6,7] Recently, Turunc and Meier [8] described the synthesis, characterization, and polymerization of monomers derived from methyl 10-undecenoate via a thiol-ene (''click'') approach.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, diverse studies have been reported on the use of various saturated fatty acid-based 2-oxazoline monomers for the preparation of well-defined (co)polymers. [4] Moreover, the synthesis and polymerization of 2-''soy-alkyl''-2-oxazoline (SoyOx) [6,18] and 2-(dec-9-enyl)-2-oxazoline (DecEnOx), which are both based on unsaturated fatty acids, has been reported. The synthesis and polymerization of DecEnOx was first described by Cai and Litt.…”
Section: Introductionmentioning
confidence: 99%